PENINGKATAN PEMBELAJARAN AKTIVITAS ATLETIK MELALUI METODE STAD KELAS V SDN WONOSARI I KECAMATAN PAGU KABUPATEN KEDIRI TAHUN 2012/2013 - Sukatman Sukatman (WAHANA, 2015)
Athletics became one of the most important activities in the learning process of physical education in elementary school because in every teaching physical education teacher always uses it in the beginning of learning activities. However, the phenomenon in the field showed a negative attitude and learning done by students. They got boredom as monotonous, tired, less fun, get bored quickly. Another thing can be seen from the students, they find shelters and speak among their friends during the learning process. So that teachers used the Student Team Achievement Division to improve the process of Teaching and Learning Activities. The focus of this study examines whether there is an increase in the value of learning in athletic activities in the long jump of fifth grade students of SDN Wonosari I – Pagu- Kediri. The research method used was Class Action Research. The subjects were students of class V and asked two observers in view of the learning process in the field. Results Showed that the first cycle of learning completeness reached only 55.55%. So there was a change in the learning process by performing some groups as the representative group to give a demo from the theory given by the teacher. In the second cycle, there was a significant increase in the value of up to 96%. So, the cycle was stopped because the quality of learning had been reached. To sum up, It can be concluded that the STAD is able to increase the value of learning in athletic activities in the long jump fifth grade students of SDN Wonosari I-Pagu-Kediri. Key words: STAD, athletics, classroom action research